Answer:
y=-6, x=4, z=1
Explanation:
1st step
3y-5z=-23
4x+2y+3z=7
-2x-y-z=-3
2nd step
4x+2 * -23+5z/3 +3z=7
-2x- -23+5z/3 -z=-3
3rd step
4x+ -46+19z/3 =7
-2x+ 23-8z/3 =-3
4th step
-2 * -19z+67/12 + 23-8z/3 =-3
5th step
z-7/ 2 =-3
6th step
x= -19 1+67/12
x=4
7th step
-23+5z/3 Substitute x=4, z=1 y=-6
Answer: x=4 y=-6 z=1
Multiply the equation (3) by 2:
Sum the equations (2) and (4):
Substitute the value of z into equation (1):
Divide both parts of the equation by 3:
Thus,
Divide both parts of the equation by -2:
6.0m questions
7.8m answers